Faktor-faktor Risiko Kejadian Malaria Pada Wilayah Penambangan Timah Di Kabupaten Bangka Tengah Provinsi Kepulauan Bangka Belitung - Sujari, Sujari; Setiani, Onny; Sulistiyani, Sulistiyani (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background : Indonesia is a tropical country which is appropriate of the mosquito vector, particularly  Anopheles. In  Java and Bali Islands malaria is still an endemic disease. Malaria in Central Bangka Regency in 2007 was reported with an Annual Malaria Incidence (AMI) of  38,07 ‰. Especially in Koba (Sub-District) , the cases were still high, and Annual Malaria Incidence (AMI) was measured at  48,1 ‰. and Annual Parasite Incidence (API) was 30,52 ‰. Hence, Central Bangka Regency was still above the National Annual Malaria Incidence (AMI) which was measured less than  30 ‰. Method : An observational retrospective research by Case Control Study Design method was done to measure the risk factor of independent variable of indoor, out door and its effect  effect on malaria incidence. The case group was people with blood specimen positive malaria while the control group was negative blood specimen. The number of patients and control groups were both 76. Data were  analyzed by using Chi-square analysis for bivariate analysis and logistic regression analysis for multivariate analysis. Result : Anopheles identification showed, that malaria vector was consisted of   Anopheles sundaicus, Anopheles letifer and Anopheles nigerrimus. The dominant species was Anopheles letifer because the population vector was more than the others. The analysis result of bivariate was demonstrated that sex was a  risk factor for malaria incidence. Six  factors were analyzed by multivariate house wall-density (OR=2,357;95% CI=1,019 – 5,452), the gauze wiring on ventilation (OR = 5,063; 95% CI = 1,925 – 13,312), the existence of water pond (OR = 4,407; 95% CI=1,542-12,591), the brush wood existence(OR = 2,693; 95% CI = 1,466 – 5,985), the usage of mosquito potion (lubricated, roasted, or sprayed) (OR = 7,169; 95% CI = 2,912 – 17,650). Conclusion : Variable that is most dominant to malaria case is the   usage of mosquito net has value p = 0,0001 with Confidence Interval ( CI) 95 % = 6,835-91,281  in tin mine region in sub district Koba Central Bangka Regency. Habit applies mosquito net at group of lower case that is 57,9 %, while at group of konrol habit applies higher mosquito net that is 90,8 %. Keywords: Endemic Area, Malaria, Risk Factor, Tin Mining Area.